Spatial density‐dependent parasitism and specificity in the robber fly Mallophora ruficauda (Diptera: Asilidae) - Castelo, Marcela Karina; Corley, Juan Carlos (Wiley, 2019)
The density‐dependence in parasitism by the robber fly Mallophora ruficauda (Diptera: Asilidae) on scarab beetle larvae (Coleoptera: Scarabaeidae) populations was studied in the present research. Mallophora ruficauda is a pestiferous species common in the open grasslands of the Pampas region of South America. Adults are predators of insects and larvae are solitary parasitoids of third instar larvae of several species of scarab beetle (Coleoptera: Scarabaeidae). In contrast with most studied host‐parasitoid interactions, host searching by M. ruficauda is carried out by both larvae and adults. Typically, robber fly females lay eggs on tall grasses from where larvae drop to the ground, and attack hosts which are buried in the soil. We carried out our study at two spatial scales close to 14 apiaries located in the provinces of Buenos Aires and Entre Ríos (Argentina). We found that parasitism is density‐independent at the larger spatial scale and inversely density‐dependent at the smaller one. We also found that M. ruficauda selects Cyclocephala signaticollis among several scarab beetle species. Specificity is observed both at large and small spatial scales. We discuss the implications of both host specificity and host searching behaviour on the observed parasitism patterns.